Tensile, barrier, dynamic mechanical, biodegerdation properties of cassava/sugar palm fibre reinforced cassava starch hybrid composites - Edhirej, Ahmed; Sapuan, S. M.; Jawaid, Mohammad; Zahari, Nur Ismarrubie (North Carolina State University, 2017)
The hybrid composite was prepared from cassava bagasse (CB) and sugar palm fiber (SPF) by casting technique using cassava starch (CS) as a matrix and fructose as a plasticizer. The chemical composition and physical properties of SPF and CB were studied in this work. SPF was added at different loadings of 2, 4, 6, and 8% dry starch to the CS/CB composite films with 6% CB. The addition of SPF influenced the hybrid properties. It was observed that the addition of 6% SPF to the composite film increased the tensile strength and modulus up to 20.7 and 1114.6 MPa, respectively. Also, dynamic-mechanical properties of the hybrid composites were investigated using a DMA test. The incorporation of SPF increased the storage modulus (E’) value from 0.457 GPa of CS to 1.490 GPa of CS-CB/SPF8 hybrid composite film. Moreover, the incorporation of SPF slightly decreased the water vapor permeability (WVP) compared to the CS/CB composites film. It can be concluded that the incorporation of SPF led to changes in cassava starch composite film properties, potentially improving the bio-degradability, WVP, and mechanical properties of the film. Based on its excellent properties, CB/SPF-CS hybrid composite films are suitable for various purposes such as packaging, automotive, and agro-industrial applications, at lower cost.